Mengagas Konsep Moderasi Islam untuk Anak Usia Dini - A’la, Moh. Rofikil; shofwan, arif muzayin; Husnah, Ziadatul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
Until now, the Islamic moderation term for early childhood is still very minimal. There are obstacles in explaining the terms of Islamic moderation in early childhood subjects, especially those who are still in the early stages of knowing the religion. Therefore, this paper tries to explore the concept of Islamic moderation for early childhood. This qualitative descriptive research uses a literature study in conducting its research. The data analysis technique uses content analysis by sorting out data according to the objectives and research problems. This paper produces several things as follows. First, Islamic moderation is a view or attitude that always tries to take a middle position from two opposing and excessive attitudes so that one of the two attitudes in question does not dominate in one's thoughts and attitudes. The basis is the hadith of the Prophet Muhammad